2016
DOI: 10.1016/j.peptides.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-occurring TGR5 agonists modulating glucagon-like peptide-1 biosynthesis and secretion

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Peptides used for pharmacological intervention have been traditionally derived from natural products isolated from plants, animals or humans (as is the case with hormone-based peptide agonists) [9,10]. However, biologically-potent peptides are increasingly mined from genetic or recombinant libraries as well as chemical and peptide screens [11].…”
Section: Introductionmentioning
confidence: 99%
“…Peptides used for pharmacological intervention have been traditionally derived from natural products isolated from plants, animals or humans (as is the case with hormone-based peptide agonists) [9,10]. However, biologically-potent peptides are increasingly mined from genetic or recombinant libraries as well as chemical and peptide screens [11].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine mechanisms of endogenous GLP-1 release may facilitate the development of selective GLP-1 agonists [41]. TGR5 is a G protein-coupled receptor on intestinal endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites are frequently associated with various medicinal actions and other forms of bioactivity—many such metabolites have been isolated and their activity characterized. Our ongoing programme of work screening natural products for antidiabetic activity [23,24,25,26,29] indicated that L.sativa (cv. Grand Rapids) contained modest levels of inhibitory activity against both α-glucosidase and DPP-4 and also stimulated secretion of the intestinal glucoregulatory hormone GLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The specific bioactivities tested were inhibition of α-glucosidase, inhibition of dipeptidyl peptidase-4 (DPP-4), and stimulation of glucagon-like peptide-1 (GLP-1) secretion (an important human intestinal hormone). These 3 anti-diabetic targets are the basis of pharmacological treatments for type 2 diabetes mellitus and it is well established that they can be modulated by natural products, nutrients and phytochemicals [14,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%